Parâmetros ecofisiológicos de sementes de Mimosa caesalpiniifolia Benth - Holanda, Alexandre Emanuel Regis (2013)
Initial seed species are sensitive to light and their germination is strongly inhibited by light filtered by vegetation. The seeds of the later successional species do not require light and the germination is enhanced by far red light. The main environmental factors that can influence the germination process are: light, temperature and water potential. Based on the assumptions of ecological succession, this study aims to evaluate the ecophysiologicals responses of seed germination of sabiá (Mimosa caesalpiniifolia Benth.) in relation to temperature, light and desiccation, for later specie introduction to recovery programs in degraded areas. The analyzes were performed with seeds collected at the Vale do Curu Experimental Farm of Federal University of Ceará - UFC, Pentecoste city – Ceará. It was determined biometrics fruit and seed and germination was evaluated at different temperatures (5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C and 10-40 ° C), types of light (white light, red light, far red light and dark) and humidities (9.04%, 6.06%, 4.68%, 3.54%, 3.10% and 3.07%). Experiment of biometrics fruit and seed the data were analyzed descriptively. The experiments of temperature, light and humidity content were conducted in a completely randomized design. It was found that the seeds have a higher germination rates at 25°C and germinated in the temperature range of 10-40°C. Seed germination is considered indifferent to light and controlled by the phytochrome using the response very low fluence (RFMB). And the seeds not suffer damage to low levels of humidity content and were classified as orthodox.